2018
DOI: 10.1101/466847
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Translationally Controlled Tumor ProteinTCTPas Peptide Vaccine againstSchistosoma japonicum: an Immunoinformatics Approach

Abstract: Schistosoma japonicum is the most pathogenic causative form of schistosomiasis that causes a major health problem in its endemic countries. Until now, praziquantel is the only drug used to treat Schistosomiasis, but it does not prevent re-infection. So, repetition of the treatment is needed. Moreover, there is no effective vaccine against S. japonicum. Therefore, an urgent need for the development of vaccines is mandatory. This study aimed to analyze an immunogenic protein, Transitionally Controlled Tumor Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…The novel diagnostic peptide candidates proposed as antigens have provided acceptable results for the neglected tropical diseases caused by cestodes (Zimic et al ., 2011; Miles et al ., 2017, 2019). Further, a research on immunoinformatic approach has shown the development of a universal peptide vaccine against Schistosoma japonicum using epitope prediction (Abdalrahman et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The novel diagnostic peptide candidates proposed as antigens have provided acceptable results for the neglected tropical diseases caused by cestodes (Zimic et al ., 2011; Miles et al ., 2017, 2019). Further, a research on immunoinformatic approach has shown the development of a universal peptide vaccine against Schistosoma japonicum using epitope prediction (Abdalrahman et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%